Mortality, Admissions, and Patient Census at SNFs in 3 US Cities During the COVID-19 Pandemic - Barnett, Michael L. (JAMA, 2020)
This study uses Medicare’s Nursing Home Compare and a university long-term care database to compare census, admissions, discharges, and mortality at skilled nursing facilities (SNFs) in 3 metropolitan areas during March-May 2020 vs March-May 2019.